Effectiveness of educational units using the Thought Acceleration Model on the learning of table tennis forehand and backhand in 13–15-year-old players - Qaddoori Ameen, Ihsan (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The aim of this research was to study the effectiveness of educational units using the Thought Acceleration Model on the learning of table tennis forehand and backhand in 13–15-year-old players. The research sample consisted of 10 junior players (ages 13-15 years) from the specialized table tennis academy of the province of Kirkuk. The researcher divided the research sample into two groups, the experimental group and the control group, each consisting of 5 players. The experimental group received 8 educational units according to the Thought Acceleration Model. The results confirmed the effectiveness of the educational units using the Thought Acceleration Model on the learning of table tennis forehand and backhand in 13–15-year-old players. Therefore, the author recommends to use educational models that address the functioning of the human mind and help activate its energies along with special exercises to develop specific skills in any given sport.